Percutaneous Sacroplasty : Effectiveness and Long-Term Outcome Predictors - Lee, Jaehyung (J Korean Neurosurg Soc, 2020)
OBJECTIVE: To evaluate the effectiveness and long-term outcome predictors of percutaneous sacroplasty (PSP). METHODS: This single-center study assessed 40 patients with sacral insufficiency fractures using the short-axis technique under C-arm flat-panel detector computed tomography (CT). Two radiologists reviewed the patients’ magnetic resonance and CT images to obtain imaging findings before PSP and determine technical success, respectively. The short-term outcomes were visual analog scale score changes and opioid usage reductions. Long-term outcomes were determined using telephone interviews and the North American Spine Society (NASS) patient-satisfaction index at least one year after PSP. RESULTS: Technical success was achieved without any significant complications in 39 patients (97.5%). Telephone interviews were possible with 12 patients and failed in 10 patients; death was confirmed in 18 patients. Fifteen patients (50%) re-visited the hospital and received conservative treatment, including spinal injections. Nine patients reported positive satisfaction (NASS patient-satisfaction index 1 or 2), while the negative satisfaction group (NASS patient-satisfaction index 3 or 4, n=3) showed a higher incidence of compression fractures at the thoracolumbar spine level (66.7% vs. 22.2%) and previous spinal injection history (66.7% vs. 33.3%). The poor response group also showed higher incidences of facet joint arthrosis (100% vs. 55.6%), central canal stenosis (100% vs. 22.2%), neural foraminal stenosis (33.3% vs. 22.2%), scoliosis (100% vs. 33.3%), and sagittal malalignment (100% vs. 44.4%). CONCLUSION: PSP was effective for sacral insufficiency fractures and showed good long-term outcomes. Combined compression fractures in the thoracolumbar spine and degenerative lumbar pathologies could be possible poor outcome predictors.